An archetypal analysis of Katniss Everdeen from The Hunger Games - Zalbidea Paniagua, Maya (Cuestiones de Género: de la igualdad y la diferencia, 2021)
Suzanne Collins’ The Hunger Games trilogy invites to reflect on the exchange of gender roles metaphorically performed by a female and male protagonists who play the warrior as well as the family protector roles. From a myth-critical theoretical framework and applying psychoanalysis in literature methodology, this article will provide a feminist analysis of The Hunger Games trilogy (2008-2020) focusing on how the protagonists, Katniss Everdeen and Peeta Mellark, deconstruct gender stereotypes. Peeta Mellark will be regarded as a future man who supports gender equality while Katniss Everdeen will be considered a representation of goddesses’ archetypes applying Carl Gustav Jung’s (1970) approach on archetypes and collective unconsciousness as well as Jean Shinoda Bolen’s (2010) theories of feminine psychology based on Greek goddesses archetypes.